Pemanfaatan Kulit Bawang Merah dan Air Cucian Beras Sebagai Pupuk Organik Cair (POC) - Wijaya, Andi Muthiah Sofiah; Ernida Mahmud; Andi Irga Satrawati Taslim (Universitas Mataram, 2024)
Utilization of shallot skin waste and rice washing water as liquid organic fertilizer (POC) in Pekalobean Village, Anggeraja District, Enrekang Regency. With the majority of the population working as farmers, the use of organic fertilizer is important to increase soil and plant fertility without damaging the environment. This community service activity involves training the Women Farmers Group on how to make POC from onion skin waste and rice washing water. The methods used include material exposure and direct practice, with the aim of reducing waste and increasing the economic value of these materials. The research results show that the POC produced contains important nutrients such as nitrogen, phosphorus and potassium, which can be easily absorbed by plants. It is hoped that this activity can provide motivation to the community to process household waste and reduce dependence on chemical fertilizers and pesticides.